Biomembrane Frontiers Nanostructures, Models, and the Design of Life - Faller, Roland.; Longo, Marjorie L.; Risbud, Subhash H.; Jue, Thomas. (Handbook of Modern Biophysics, 2009)
HANDBOOK OF MODERN BIOPHYSICS Series Editor Thomas Jue, PhD Handbook of Modern Biophysics brings current biophysics topics into focus, so that biology, medical, engineering, mathematics, and physical-science students or researchers can learn fundamental concepts and the application of new techniques in addressing biomedical challenges. Chapters explicate the conceptual framework of the physics formalism and illustrate the biomedical applications. With the addition of problem sets, guides to further study, and references, the interested reader can continue to explore independently the ideas presented. Volume II: Biomembrane Frontiers: Nanostructures, Models, and the Design of Life Editors: Roland Faller, PhD, Thomas Jue, PhD, Marjorie L. Longo, PhD, and Subhash H. Risbud, PhD In Biomembrane Frontiers: Nanostructures, Models, and the Design of Life, prominent researchers have established a foundation for the study of biophysics related to the following topics: Perspectives: Complexes in Liquids, 19002008 Molecular Theory Applied to Lipid Bilayers and LipidProtein Interactions Membrane Elasticity and Mediated Interactions in Continuum Theory: A Differential Geometric Approach Structure and Dynamics of Lipid Monolayers: Theory and Applications Multiscale Modeling of Supported Lipid Bilayers Collective Dynamics in Lipid Membranes: From Pore Formation to Flip-Flops Spatiotemporal Organization of Spin-Coated Supported Model Membranes Nanopore Analysis of Nucleic Acids: Single-Molecule Studies of Molecular Dynamics, Structure, and Base Sequence Complex Applications of Simple FRAP on Membranes Punching Holes in Membranes: How Oligomeric Pore-Forming Proteins and Lipids Cooperate to Form Aqueous Channels in Membranes Morphogens, Membranes and Mechanotransduction in Articular Cartilage Lifecycle of a Lipoprotein from a Biophysical Perspective Targeting Apolipoproteins in Magnetic Resonance Imaging About the Editors The editors are internationally recognized biomembrane experts and have published extensively on the structure, dynamics, and function of model and cellular membranes. Roland Faller is an Associate Professor and the Joe & Essie Smith Endowed Chair in the Department of Chemical Engineering & Materials Science at the University of California Davis. He develops and uses modern molecular simulation techniques for soft condensed matter systems, particularly biomembranes. Thomas Jue is a Professor in the Department of Biochemistry and Molecular Medicine at the University of California Davis. He develops and applies magnetic resonance techniques to study biochemical regulation in vivo. Marjorie L. Longo is a professor in the Department of Chemical Engineering and Materials Science at the University of California Davis. She applies microscopy techniques to study surface and transport properties of lipid bilayers and monolayers. Subhash H. Risbud is the Blacutt-Underwood Distinguished Professor of Materials Science in the Department of Chemical Engineering and Materials Science at the University of California at Davis and a Visiting Professor at Stanford University. His group develops new materials for nano- and biotechnology. The materials include glasses, ceramics, and nanoporous substrates for biological membranes.